Mendorong partisipasi perempuan dalam pengelolaan hutan kemasyarakatan Bura Sendana melalui pembentukan Kelompok Wanita Tani (KWT) - Kasmiati; Utami A, Widyanti; Ikawati; Dewi, Suryani (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2024)
Based on the results of observations and interviews with our partners, namely the community around the Social Forestry area, Bura Sendana State of Community Forestry (Hutan Kemasyarakatan/HKm) located in Tallambalao Village, Majene Regency, West Sulawesi, it was found that currently, females do not play an optimal role in management of forest products because there are no particular institutions for women. Therefore, women cannot access various formal sources of assistance, information, or capital provided by government agencies, private and other supporting institutions such as non-governmental organizations (NGOs), or universities. Therefore, it is essential to form formal institutions specifically for women. So, the community service partnership activity that we carry out is encouraging the establishment of a Women's Farmers Group (KWT) to manage the Bura Sendana social forestry area. This initiative is expected to support empowered female farmers from a cultural and institutional perspective. Become a pioneer in managing agricultural products from forest areas, which can improve the welfare of people in villages around forest areas in the long term. The main objective of this Community Partnership Program activity is to form a KWT to manage HKM Bura Sendana. Furthermore, we designed a participatory training to strengthen the KWT institutions that have been formed.